Normative-Consequential Structures and Moral Dilemma Limitations in Islamic Social Ethics: A Developmental Analysis of Phase F Instructional Materials - Supriyanto, Supriyanto; Al-Aqsha, Andi Qadri (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This research identifies the normative-consequential structures and the scarcity of moral dilemmas in Phase F Islamic Social Ethics materials, analyzed through Piagetian and Kohlbergian developmental frameworks. Utilizing a qualitative content analysis approach, the study evaluated the 2021 Grade XI PAI textbook and official curriculum standards, coding 508 meaning units based on five distinct moral reasoning indicators. Results indicate that instructional content is heavily weighted toward the